Pengaruh Service Quality, Store Atmosphere, dan Price Fairness terhadap Customer Satisfaction dan Customer Loyalty pada Haidilao Mall Taman Anggrek - Wijaya, Haggi Setia (Journal of Business & Applied Management, 2024)
Every corporation or business entity operating in any field of business naturally aims to obtain profit. To achieve this goal, companies will pay attention to factors that can encourage customers to make purchases. This study aims to investigate the influence of Service Quality, Store Atmosphere, Price Fairness, Customer Satisfaction, and Customer Loyalty. The research gathered 126 samples through questionnaire distribution. It is a quantitative study of descriptive nature, employing a Likert scale for questionnaire measurement. Additionally, the researcher utilized data analysis techniques including two tests: outer model testing consisting of convergent validity, discriminant validity, and reliability testing, and inner model testing including R Square and path analysis significance testing using SmartPls 3 software. The findings indicate that Service Quality and Store Atmosphere significantly influence Customer Satisfaction, while Customer Satisfaction significantly affects Customer Loyalty. However, Price Fairness does not significantly influence Customer Satisfaction. Future research is encouraged to explore different objects, variables, and further theoretical discussions.